Molecular prevalence of HBB-associated hemoglobinopathy among reproductive-age adults and the prenatal diagnosis in Jiangxi Province, southern central China - Luo, Haiyan; Huang, Ting; Lu, Qing; Zhang, Liuyang; Xu, Yonghua; Yang, Yan; Guo, Zhen; Yuan, Huizhen; Shen, Yinqin; Huang, Shuhui; Yang, Bicheng; Zou, Yongyi; et al. (Frontiers in Genetics, 2022)
Background and aims: Hemoglobinopathy associated with the HBB gene, with its two general subtypes as thalassemia and abnormal hemoglobin (Hb) variants, is one of the most prevalent hereditary Hb disorders worldwide. Herein, we aim to elucidate the prevalence of β-thalassemia and abnormal hemoglobin variants and the prenatal diagnosis of the HBB gene in Jiangxi Province, central China. Methods: Hematological indices and capillary Hb electrophoresis were conducted for 136,149 subjects who were admitted to Jiangxi Maternal and Child Health Hospital and requested for hemoglobinopathy investigation. Routine α- and β-globin genotyping was performed by Gap-PCR and Dot-RDB for the 11,549 individuals suspected to be thalassemia carriers. For participants whose genotypes could not explain their hematological indices, further Sanger sequencing and Gap-PCR were conducted for the detection of rare or novel variants in related globin genes. Prenatal diagnosis was performed for 77 pregnant couples both carrying β-thalassemia trait at appropriate gestational ages. Results: Among the 11,549 subjects, 2,548 individuals were identified with HBB-associated hemoglobinopathy based on molecular analysis. A total of 2,359 subjects were identified as β-thalassemia heterozygous carriers and nine cases were diagnosed as compound heterozygous β-thalassemia. Additionally, 125 cases were detected with composite α- and β-thalassemia and the remaining 56 individuals with abnormal Hb variants in the HBB. A total of 35 types of variants were identified in the HBB gene, including 26 types of β-thalassemia and nine types of abnormal Hb variants. Four novel variants were firstly reported, including one variant in HBA2 and three variants in HBB. Overall, 77 prenatal samples underwent β-thalassemia molecular diagnosis; 20 fetuses were identified with normal β-thalassemia genotypes, 30 fetuses with β-thalassemia heterozygote, 11 with homozygote, and 16 with double heterozygote in HBB. Conclusions: For the first time, we demonstrate a relatively high prevalence of β-thalassemia and abnormal Hb variants (1.872%) among a large child-bearing population in the Jiangxi area of central China. The detection of a rare or novel β-thalassemia mutation is significant in clinical genotyping analysis to avoid misdiagnosis of β-thalassemia. Prenatal diagnosis is an effective way to prevent and control birth defects of β- thalassemia.